Mixing ratios of trace gases in the austral polar atmosphere during August and September of 1987 - Pollock, Walter H.; Lueb, Richard A.; Henry, Bruce E.; Heidt, Leroy E.; Vedder, James F. (1988)
Mixing ratios are presented for a number of long-lived trace gases in the austral polar atmosphere during August and September of 1987. The recent discovery of a 12-year trend of increasing depletion of ozone over the Antarctic Continent in the spring of each year led to numerous theoretical interpretations and several scientific expeditions to the region. The results herein were obtained as part of a major effort involving penetration of the region of ozone depletion by NASA's multi-instrumented aircraft. One of the 14 instruments on the high-altitude ER-2 aircraft collected pressurized air samples between latitudes of 53 degrees and 72 degrees south at pressure altitudes up to 21 km in a series of 12 flights from Punta Arenas, Chile, over the Palmer Peninsula. The sampling system, located in the nose section of ER-2, has an inlet tube in the free airstream, a metal-bellows air pump, and 14 specially treated 1.6 l stainless-steel canisters for containing the pressurized air at 350 kPa. A typical flight profile consisted of a southbound path on the 428 K potential temperature surface, a descent to a pressure altitude of 13.7 km, a climb to the 460 K surface, and return on this surface. Mixing ratios for the trace gases were obtained from gas chromatographic analyses of the pressurized air samples. Of the species measured, the mixing ratios for CH4, CO, N2O, CF2 Cl2, CFCl3, CH3, CCl3, CCl4, and C2F3Cl3 are reported here.